Inner Purification and Divine Love: The Spiritual Essence of Sufism - Nadri Taja (West Science Islamic Studies, 2026)
This article examines the spiritual essence of Sufism through two central concepts: inner purification and divine love. The study addresses contemporary challenges characterized by a crisis of meaning, existential anxiety, materialism, and a decline in spiritual depth. Employing a qualitative approach based on literature review, the article analyzes both classical and contemporary Sufi sources to explore the relationship between tazkiyat al-nafs and mahabbah ilahiyyah. The findings indicate that inner purification constitutes a transformative process that cleanses the heart of egoism, arrogance, envy, and excessive worldly attachment. Meanwhile, divine love serves as the highest orientation, guiding individuals toward closeness to God, sincere worship, and the cultivation of virtuous character. The two concepts are interdependent: love for God necessitates a purified heart, while inner purification attains its deepest significance through divine love. The article underscores the continued relevance of Sufism for modern society, as it provides a spiritual pathway that integrates inner tranquility, moral awareness, and social responsibility in daily life. These findings contribute conceptually to the study of Islamic spirituality and reinforce the significance of Sufism as a paradigm for ethical, reflective, and transformative self-development within a meaningful and enduringly religious modern civilization.